Study on nitrogen demand model in pakchoi (Brassica campestris ssp. Chinensis L.) based on nitrogen contents and phenotypic characteristics - Chang, Liying; Xiong, Xin; Hameed, Muhammad Khalid; Huang, Danfeng; Niu, Qingliang (Frontiers in Plant Science, 2023)
In precision agriculture, the diagnosis of nitrogen (N) nutrition status based on plant phenotype, combined effects of soil types, agricultural practices, and environmental factors are essential for plant N accumulation, which helps to assess the N supply in plants at the right time and amount to ensure high N fertilizer use efficiency by reducing the N fertilizer applications and minimizing environmental pollution. For this purpose, three different experiments were performed. A critical N content (Nc) model was constructed based on cumulative light and temperature (LTF), N applications, and cultivation systems on yield and N uptake in pakchoi. According to the model, aboveground dry biomass (DW) accumulation was found equal or below to 1.5 t/ha, and the Nc value was observed at a constant of 4.78%. However, when DW accumulation exceeded 1.5 t/ha, Nc declined with the increase of DW accumulation, and the relationship between Nc and DW accumulation developed with the function: Nc %=4.78 x DW-0.33. A nitrogen demand model was established based on the multi-information fusion method, which integrated multiple factors, including Nc, phenotypical indexes, the temperature during the growth period, photosynthetically active radiation, and N applications. Furthermore, the model’s accuracy was verified, and the predicted N contents were consistent with the measured values (R2=0.948 and RMSE=1.96 mg/plant). At the same time, an N demand model based on N use efficiency was proposed. This study can provide theoretical and technical support for precise N management in pakchoi production.